Long term response of electrochemotherapy with reduced dose of bleomycin in elderly patients with head and neck non-melanoma skin cancer - Jamšek, Črt (Radiology and oncology (Ljubljana), 2020)
. Electrochemotherapy (ECT) is a local cancer treatment based on electroporation where the electric field is used to enhance cell membrane permeability and thereby facilitating the transition of chemotherapeutic agents into the cell. For the treatment of non-melanoma skin cancer, a standard dosage of 15,000 IU/m2 bleomycin (BLM) is used. The aim of the present study was to evaluate the long-term ECT response in the group of elderly patients with non-melanoma skin cancer treated with a reduced dose of BLM in comparison to the outcome in the patients treated with the standard dose of BLM. Patients and methods. Twenty-eight patients older than 65 years, with a total of 52 non-melanoma skin lesions were included in the study. Twelve patients (24 lesions) in the experimental group received a reduced dose of BLM (10,000 IU/m2), 16 patients (28 lesions) were treated with a standard dose of BLM (15,000 IU/m2). Results. No statistically significant difference in tumor control was observed between both groups. In the experimental group, tumors recurred in 39.0% of treated lesions in a median follow-up time of 28 months. In the control group, the recurrence rate of treated lesions was 15.4% in a median follow-up time of 40 months. Conclusions. ECT with a reduced dose of BLM is a feasible treatment option for elderly patients with equal efficacy to standard dose treatment and should be considered as a treatment modality in advanced aged patients with comorbidities, where overall life expectancy is poor
Keywords: elektrokemoterapija; maligni melanom; psi; ustna votlina; zdravljenje